Nano-scale coating wear measurement by introducing Raman-sensing underlayer. (10th January 2022) - Xu, Nan; Wang, Chun; Yang, Liuquan; Barimah, Eric Kumi; Jose, Gin; Neville, Anne; Morina, Ardian
Highlights: Accurate coating wear quantification at nanoscale level is established by employing a Raman sensing layer (silicon) under target coating and successfully applied to quantify the wear of target coating in dry and oil-lubricated conditions. This approach can effectively avoid the remarkable errors caused by tribo-induced effects in the interface regions, demonstrating its advantage in the capacity of error tolerance. Abstract: For gaining fundamental insight into coating wear mechanisms and increasing operational efficiency and automation degree of equipment in important application fields of coating techniques, it is of great importance to developing novel wear measurement techniques enabling nanoscale studies of coating wear in the running process, but this remains a significant challenge. Here, a facile strategy is reported to achieve accurate coating thickness quantification at nanoscale level, which is based on a bilayer structure: a top target layer of a-C:H (hydrogenated amorphous carbon) film is considered as a light attenuating and anti-wear layer while underlayer of silicon serves as Raman-sensing layer. Through constructing the relationship between the thickness of a-C:H and Raman intensity of attenuated silicon signal, the coating thickness quantification method is established and successfully applied to quantify coating wear in the friction process. This approach can effectively avoid remarkable errors caused by tribo-induced effects in the interface regions, demonstrating its advantage in error tolerance. Details about these tribo-induced effects are also elucidated by a combination of Raman spectroscopy, optical profilometer, EELS, and TEM. In particular, the proposed approach enables the possibility of measuring coating wear with oil film on top, which breaks an important limitation of existed wear measurement methods, i.e., incapable of applying in oil-lubricated conditions. This approach can be used to quantify the wear condition of diverse target coatings and has the potential of online wear monitoring when combining a compact laser excitation and detection system. Graphical abstract: Image, graphical abstract